2007
DOI: 10.1186/1744-859x-6-16
|View full text |Cite
|
Sign up to set email alerts
|

Arachnoid cyst in a patient with psychosis: Case report

Abstract: BackgroundThe aetiology of a psychotic disturbance can be due to a functional or organic condition. Organic aetiologies are diverse and encompass organ failures, infections, nutritional deficiencies and space-occupying lesions. Arachnoid cysts are rare, benign space-occupying lesions formed by an arachnoid membrane containing cerebrospinal fluid (CSF). In most cases they are diagnosed by accident. Until recently, the coexistence of arachnoid cysts with psychiatric disturbances had not been closely covered in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
31
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 25 publications
5
31
0
Order By: Relevance
“…We hypothesized that the patient's psychopathological symptoms did not respond to clozapine medication due to the relatively large size of the cerebral lesion. Our speculation is consistent with the assumptions proposed by previous case reports [1][2][3][4][5][6][7][8][9][10]. Recently, Baquero and colleagues presented the case of an arachnoid cyst-related psychotic disorder is remitted in terms of the psychotic symptoms [19].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We hypothesized that the patient's psychopathological symptoms did not respond to clozapine medication due to the relatively large size of the cerebral lesion. Our speculation is consistent with the assumptions proposed by previous case reports [1][2][3][4][5][6][7][8][9][10]. Recently, Baquero and colleagues presented the case of an arachnoid cyst-related psychotic disorder is remitted in terms of the psychotic symptoms [19].…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that reduced cerebral lateralization may have given rise to the symptomatology in our patient [3][4][5][6]. This case further suggested that reduced brain lateralization might also contribute to the refractoriness of schizophrenia to clozapine and other antipsychotic medications.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Arachnoid cysts can cause many different neuropsychiatric symptoms depending on their location. All of these effects and symptoms are caused either by compression of the cyst on the surrounding brain tissue or interference with the functions of the surrounding neurologic structures (da Silva et al 2007;Wester, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Arachnoid cysts most commonly present during childhood and are usually identified incidentally. About 75% of intracranial arachnoid cysts presented before 3 years of age in one series [5]. The most common symptoms include headache and seizures.…”
mentioning
confidence: 99%